LoRa: A Proposed Connectivity Technology for Internet of Things Applications in the Kurdistan Region of Iraq - Ahmad, Sarko Salahadin; Saeed, Bakhtiar Ibrahim (Kurdistan Journal of Applied Research, 2021)
The Internet of Things (IoT) has become one of the most important trends of this century. Recent advances in many different communication technologies and protocols, and access to low-cost and low-power microcontrollers and sensors have made it more prevalent. Globally, most IoT adoption comes from developed countries such as the United States, United Kingdom, Western Europe, and East Asia, as these countries have a well-established nationwide IoT infrastructure. In contrast, the IoT application in developing countries such as Kurdistan Region of Iraq (KRI) remains restricted as deployment faces main challenges. On the one hand, selecting the right technology for IoT applications can be complicated with so many IoT connectivity technologies such as Cellular, Wi-Fi, Low Power Wide Area Network (LPWAN), Bluetooth, and ZigBee on the market. On the other hand, the main impediment seems to be the lack of IoT infrastructure technologies in developing countries. In this paper, a comparative study on the main LPWAN technologies has been carried out in terms of cost and coverage of the network and range to become connectivity technology for IoT applications in the KRI. Based on the study, LoRa technology has been presented and proposed as the optimal connectivity technology to establish an IoT infrastructure for the KRI. The proposed network enables the deployment of IoT applications easier and faster. In addition, various LoRa based IoT applications have been proposed that benefit many sectors. A potential application has been set out as a case study to show case the significance of the new infrastructure. The proposed LoRaWAN infrastructure can accommodate a vast range of applications and will revolutionize IoT applications in the KRI as it enables data transmission over a long distance while using extremely low power.